DUKUNGAN PASANGAN PADA PASIEN CA PAYUDARA YANG MENJALANI KEMOTERAPI DI RSI SULTAN AGUNG SEMARANG - Tri Nurhidayati; Desy Ariyana Rahayu (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Breast cancer is a disease that can affect anyone, especially in women, and any type of treatment ofbreast disease can cause physiological, psychological and social problems in women affected by this disease. Changes in body image due to physical changes that accompanied the treatment that has been found to be a very stressful psychological response for breast cancer patients, this disease has made the women affected by cancer experienced anxiety about the treatment process that willbe on the way later so tend to affect self-concept women who can ultimately affect interpersonal relationships with others and included in their own spouse (Nuracmah, 2005).This study aims to determine the support of couples in Ca breast patients who underwent chemotherapy. The design of this research is qualitative research using descriptive phenomenology approach by doing direct exploration, analyze and describe the support of the couple. In this studycouples support consists of instrumental support, award support, emotional support, and information support. The  four support that had  founded that needs attention is informational support. The couple is expected to be able to provide informational support to the dean actively inquiring to the doctor or nurse during chemotherapy